1990
DOI: 10.1016/0032-3861(90)90397-h
|View full text |Cite
|
Sign up to set email alerts
|

Segmented block copolymers based on polyamide-4,6 and poly(propylene oxide)

Abstract: Segmented copolymers were obtained through copolymerization of polyamide-4,6 and poly(propylene oxide) (PPOx). An amine-terminated PPOx ('soft') segment of molar mass 430 was reacted with nylon-4,6 salt in an autoclave (30min, 210°C, 7 bar). In this reaction a prepolymer was prepared, which was postcondensed afterwards. In ethanol, a considerable amount of material could be extracted from the solid copolymers of low polyamide content. Extractability was found to be strongly reduced with increasing polyamide co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…For PPG-based TPAEs, monomer casting PA6 modified with maximum 6 wt % of this polyetheramine shows an obvious decrease in crystallization ability and an elastic deformation behavior [30]. Grymans et al selected PA46 salt and PPG diamine to prepare PA46-PPG segmented copolymers via condensation followed by solid-phase polycondensation [31]. However, severe macro-phase separation occurs despite adding m-cresol as solvent.…”
Section: Introductionmentioning
confidence: 99%
“…For PPG-based TPAEs, monomer casting PA6 modified with maximum 6 wt % of this polyetheramine shows an obvious decrease in crystallization ability and an elastic deformation behavior [30]. Grymans et al selected PA46 salt and PPG diamine to prepare PA46-PPG segmented copolymers via condensation followed by solid-phase polycondensation [31]. However, severe macro-phase separation occurs despite adding m-cresol as solvent.…”
Section: Introductionmentioning
confidence: 99%
“…) . The T6T6T segments have been incorporated into hydrophobic polyether‐based copolymers such as polytetramethyleneoxide (PTMO), polyethyleneoxide block copolymers, poly(2,6 dimethylphenylene ether), and polysufhone . After incorporation of tetraamide units into the amorphous polymers, the polymer becomes semicrystalline materials having high crystallinity with high crystallization rates.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, since the chain‐length distribution of commercially available poly(propylene oxide) (PPO) oligomers is much narrower than that of PTMG oligomers, Hutten et al. [ 32 ] fabricated TPAEs via employing PPO in place of PTMG as the soft segment. It is demonstrated that the lower limit of the rubber region for this TPAE decreases with the increase of PPO content.…”
Section: Synthesis Of Tpaesmentioning
confidence: 99%